Treated and highly diluted, but wastewater still impacts diversity and energy fluxes of freshwater food webs - de Guzman, Ioar (2023)
Wastewater treatment plants (WWTPs) have greatly improved water quality globally. However, treated effluents still contain a complex cocktail of pollutants whose environmental effects might go unnoticed, masked by additional stressors in the receiving waters or by spatiotemporal variability. We conducted a BACI (Before-After/Control-Impact) ecosystem manipulation experiment, where we diverted part of the effluent of a large tertiary WWTP into a small, unpolluted stream to assess the effects of a well-treated and highly diluted effluent on riverine diversity and food web dynamics. We sampled basal food resources, benthic invertebrates and fish to search for changes on the structure and energy transfer of the food web with the effluent. Although effluent toxicity was low, it reduced diversity, increased primary production and herbivory, and reduced energy fluxes associated to terrestrial inputs. Altogether, the effluent decreased total energy fluxes in stream food webs, showing that treated wastewater can lead to important ecosystem-level changes, affecting the structure and functioning of stream communities even at high dilution rates. The present study shows that current procedures to treat wastewater can still affect freshwater ecosystems and highlights the need for further efforts to treat polluted waters to conserve aquatic food webs.